Case Study on working of SWIGGY - Prashar, Kirti; Bawa, Simerjeet Singh; Kaur, Tanveer (Gyan Management Journal, 2022)
India is young developing country and has lot of potential which is yet untapped.  Food business is one of them. Covering that gap Swiggy and is growing day  by day and expanding business to large scales. Swiggy is a customer oriented  company, and has online platform to improve the experience of food delivery.  Swiggy by improving consumer experience and shrinking delivery time is on  a path to become the leader of food delivery business.
Keywords: Swiggy; Business Schemes; Financial options; Business Model; Food delivery business; Funding Opportunities